Perceptions of Teaching Factors Among Public Elementary Teachers - Henry, Balabal (International Journal of Sustainability and Advanced Integrated Research, 2026)
Teaching factors play a crucial role in shaping teachers’ instructional quality and teaching performance. This study, therefore, examined the teaching factors: pedagogical planning, teaching effectiveness, personal attributes, professional conduct, and management skills that may have influenced the teaching performance of local elementary teachers. It also examined whether these factors differ across demographic profiles. The study employed a descriptive-survey design. Data were collected using a validated and reliable questionnaire. It involved 68 public elementary teachers from the Division of Ifugao, Philippines. Results revealed that the teachers generally perceived all teaching factors as excellent. Professional conduct was ranked the topmost, followed by teaching effectiveness and personal attributes, both tied at the second rank. Pedagogical planning ranked fourth, while management skills ranked last. Further, results showed no significant differences in teachers’ perceptions across gender, educational attainment, or number of years of service. However, personal attributes varied significantly among age groups. The study implies that the teaching factors were consistently valued, but professional growth strategies may need to be tailored according to career stage. The study recommends implementing inclusive professional development programs that foster mentorship, reflective practice, and collaborative learning, supporting novice and experienced teachers. By prioritizing ongoing skill enhancement and equitable support, schools can strengthen teaching effectiveness, promote professional growth, and ultimately enhance student learning outcomes across all classrooms. Further related research is encouraged.